Community Participation in Village Development from Islamic Economic Perspectives - Mutiara, Nisa; Mursinto, Djoko; Maliki, Zainuddin (Journal of Innovation in Business and Economics, 2019)
The implementation of the Law No. 6 of 2014 and the Village Fund in 2015 was able to encourage community participation in the entire development process starting from planning, implementation, supervision and utilization. This study aimes to analyze community participation in Megaluh Village by using an Islamic perspective. This study applied a case study approach to community participation and a literature review to determine community participation after the implementation of the Village Law from an Islamic economic perspective which are called maqhasid sharia. In general, Megaluh villages have shown active community participation in village development, but they still need to carry out long-term planning to ensure prosperity and this has not been observed during the study.